We meet again ebook - Pastis, Stephan (Timmy Failure, 2014)
From the New York Times best-selling creator of Timmy Failure comes a third adventure about the comically overconfident sleuth. His name is Failure. Timmy Failure. And his detective agency is on the verge of global domination. Global riches. Global fame. And yet the gods keep throwing him curveballs: for starters, academic probation. The coveted Miracle Report is the key to everything, including a good grade. It's dirty business. It's best you know nothing. But one thing is for sure: Timmy Failure will be triumphant again!